Angular distribution and polarization of characteristic x-ray lines following innershell photoionization of tungsten by linearly polarized light. (March 2020) - Zhang, D.H.; Dong, C.Z.; Wu, Z.W.
Highlights: Angular distribution and linear polarization of the characteristic Lα1 (3d5/2 → 2p3/2 ) and Lα2 (3d3/2 → 2p3/2 ) lines following the innershell 2p3/2 photoionization of tungsten by linearly polarized light are studied within the framework of the density matrix theory. Abstract: The innershell 2 p 3/2 photoionization of tungsten by linearly polarized light has been investigated, together with the subsequent Lα 1 (3 d 5/2 → 2 p 3/2 ) and Lα 2 (3 d 3/2 → 2 p 3/2 ) radiative decays. In particular, a specific density matrix formalism is presented for the photoionization and decay process to explore how the linear polarization of the incident ionizing light influences the photoionization process as well as the angular and polarization properties of the emitted characteristic Lα 1, 2 photons. Detailed calculations show that the alignment parameter A 20 of the 2 p 3/2 hole state is independent of the polarization of the ionizing photons, while the parameters A 2 ± 2 behave proportional to the polarization. It is found that the Lα 1, 2 characteristic lines become stronger polarized for linearly polarized incident light with the degree P = − 1, when compared with the results in Ref. [Phys. Rev. A 93, 033409 (2016)] for initially unpolarized light, while the characteristic lines become unpolarized for P = 1 . It is also found that the Lα 1, 2 angular distributions are isotropic for the case of P = − 1, while they become anisotropic for P = 0 and 1.